Deportes : the making of a sporting Mexican diaspora - Alamillo, José M., 1969- (Latinidad., 2020)
"Spanning the first half of the twentieth century, Deportes uncovers the hidden experiences of Mexican male and female athletes, teams and leagues and their supporters who fought for a more level playing field on both sides of the border. Despite a widespread belief that Mexicans shunned physical exercise, teamwork or "good sportsmanship," they proved that they could compete in a wide variety of sports at amateur, semiprofessional, Olympic and professional levels. Some even made their mark in the sports world by becoming the "first" Mexican athlete to reach the big leagues and win Olympic medals or world boxing and tennis titles. These sporting achievements were not theirs alone, an entire cadre of supporters-families, friends, coaches, managers, promoters, sportswriters, and fans-rallied around them and celebrated their athletic success. The Mexican nation and community, at home or abroad, elevated Mexican athletes to sports hero status with a deep sense of cultural and national pride. Alamillo argues that Mexican-origin males and females in the United States used sports to empower themselves and their community by developing and sustaining transnational networks with Mexico. Ultimately, these athletes and their supporters created a "sporting Mexican diaspora" that overcame economic barriers, challenged racial and gender assumptions, forged sporting networks across borders, developed new hybrid identities and raised awareness about civil rights within and beyond the sporting world"--